Les enjeux de la bataille de Mânû (283/896) - Virginie Prevost (Revue des Mondes Musulmans et de la Méditerranée)
In May 896, the Aghlabid army led by Ibrâhîm II crushed the Ibâḍî Nafûsa in Mânû on Coastal Tripolitania. After this battle, several other military campaigns were launched in the Djebel Nafûsa and in Southern Tunisia (Qanṭrâra and Nafzâwa). The battle of Mânû represents an important element of memory for Ibâḍism in North Africa and a crucial turning point in their history, often connected by Ibâḍî historians to the fall of the Imamate of Tâhart. This article, while retracing the conduct and the consequences of this event, is also focusing on the composition and evolution of Ibâḍism in North Africa during this period. It also offers a comparison between the different accounts available in Ibâḍî and Malikî sources to better emphasize the importance of this event in the historical memory of the Maghreb.